PlotCam: A handheld proximal phenomics platform - Morrison, Malcolm J.; Gahagan, A. Claire; Hotte, T.; Lefebvre, M. B.; Kenny, M.; Saumure, A. (Frontiers in Physics, 2023)
Future crop varieties must be higher yielding, stress resilient and climate agile to feed a larger population, and overcome the effects of climate change. This will only be achieved by a fusion of plant breeding with multiple “omic” sciences. Field-based, proximal phenomics assesses plant growth and responses to stress and agronomic treatments, in a given environment, over time and requires instruments capable of capturing data, quickly and reliably. We designed the PlotCam following the concepts of cost effective phenomics, being low-cost, light-weight (6.8 kg in total) and portable with rapid and repeatable data collection at high spatial resolution. The platform consisted of a telescoping, square carbon fiber unipod, which allowed for data collection from many heights. A folding arm held the sensor head at the nadir position over the plot, and an accelerometer ensured the sensor head was level at the time of data acquisition. A computer mounted on the unipod ran custom software for data collection . RGB images were taken with an 18 MP, WiFi controlled camera, infrared thermography data was captured with a 0.3 MP infrared camera, and canopy height measured with a 0.3 MP stereo depth camera. Incoming light and air temperature were logged with every image. New operators were quickly trained to gather reliable and repeatable data and an experienced operator could image up to 300 plots per hour. The PlotCam platform was not limited by field design or topography. Multiple identical PlotCams permitted the study of larger populations generating phenomic information useful in variety improvement. We present examples of data collected with the PlotCam over field soybean experiments to show the effectiveness of the platform.